The Returns of Investment on Infrastructure in China’s Urban Areas: A Comprehensive Analysis - Xue, Baichuan (International Journal of Global Economics and Management, 2024)
With economic globalisation accelerating, more and more countries and regions have begun to pay attention to infrastructure development. Infrastructure is an important support for national development, including in the areas of energy, transport and telecommunications. However, the investment and return mechanisms of infrastructure projects often present significant challenges. Due to the long-term and high-risk nature of infrastructure projects, the development and implementation of their business models and return mechanisms require special analyses. Based on the discussion of the characteristics of environmental infrastructure, this paper combines the current investment models of environmental infrastructure projects to sort out and summarise the situation of project return mechanisms in practice.